2001
DOI: 10.1051/vetres:2001127
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of thermophilic Campylobacter

Abstract: -Campylobacter has become the leading cause of zoonotic enteric infections in developed and developing countries world-wide. Antimicrobial resistance has emerged among Campylobacter mainly as a consequence of the use of antimicrobial agents in food animal production. Resistance to drugs of choice for the treatment of infections, macrolides and fluoroquinolones has emerged as a clinical problem and interventions to reduce this are recommended. Resistance to fluoroquinolones and macrolides is mediated by chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
134
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 65 publications
5
134
0
5
Order By: Relevance
“…The incidence of resistance to most of the tested antimicrobial agent in this study was generally higher for C. jejuni than for C. coli (Table 1). This finding confirmed what has been previously described (8,24), although results from another study demonstrated that C. coli was generally more resistant than C. jejuni (9,18,23,25). Owing to the increased reporting of antimicrobial resistance in Campylobacter worldwide, attempts should be made to control their use in animal husbandry.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of resistance to most of the tested antimicrobial agent in this study was generally higher for C. jejuni than for C. coli (Table 1). This finding confirmed what has been previously described (8,24), although results from another study demonstrated that C. coli was generally more resistant than C. jejuni (9,18,23,25). Owing to the increased reporting of antimicrobial resistance in Campylobacter worldwide, attempts should be made to control their use in animal husbandry.…”
Section: Discussionsupporting
confidence: 87%
“…Food-producing animals, including cattle and pigs, may be a source of such resistant isolates that are transmitted to humans by food of animal origin (Aarestrup and Engberg 2001, Ghafir et al 2007, Sheppard et al 2009, Egger et al 2012, Quintana-Hayashi and Thakur 2012. This applies particularly to strains resistant to quinolones and erythromycin, widely used for therapy in severe human infections or in immuno-compromised patients (Aarestrup and Engberg 2001).…”
Section: Introductionmentioning
confidence: 99%
“…isolated from humans has become allarming (Bywater et al, 2004;Cardinale et al, 2002). Emergence of the resistant strains coincided with the beginning of macrolides use, for the most part thylosine, in veterinary medicine, mainly in swine farming ( Aarestrup and Engberg, 2001;Luber et al, 2003).…”
Section: Introductionmentioning
confidence: 99%